PENGARUH MODEL PROJECT BASED LEARNING TERHADAP HASIL BELAJAR PEMBELAJARAN TEMATIK SISWA KELAS V DI SD N REJOWINANGUN 1 - Tunjung Sekarwangi; Kristi Wardani (Universitas Sarjanawiyata Tamansiswa, 2018)
The purpose of descriptive research is to know the tendency of student learning outcomes on V class thematic learning that is taught using project based learning model and inquiry model, comparative to know the difference of student learning outcomes on thematic learning between taught using project based learning and inquiry model. Type of research used is quasi experiment. Techniques of collecting data using tests and documentation. Data analysis techniques used descriptive analysis, prerequisite analysis test (homogeneity test and normality test) and hypothesis test using t test. This research was done in SD N Rejowinangun 1 with sample of class VB and VC with total 54 students. The result of descriptive research shows that (1) the tendency of student learning outcomes in V class thematic learning taught using project based learning model is high, while the inquiry model is low. (2) there is a very significant difference of thematic learning result among students by using project based learning model and inquiry model Â = 6.134 with p = 0.000, p value = 0,00 <0.05. It can be concluded that by looking at the average of learning outcomes, the project based learning model has an effect on student learning outcomes compared to the inquiryÂ model.